STRATEGI PENANGANAN ANAK JALANAN DI DINAS SOSIAL PEMUDA DAN OLAHRAGA KOTA SEMARANG - Wulandari Asril; Thalita Rifda Khaerani (Journal of Public Policy and Management Review, 2017)
Semarang City is the capital of Central Java province that not separated from social issues, for example is the problem of street chidren. In order to handle the problem of street Children in Semarang city, Social Department of Youth and Sports commit various activities to prevent and control the number of street children. Handling problem of street children by the Social Department of Youth and Sports in Semarang City done by field with social welfare problems.The focus and goals in this study is to formulate the strategy to handling the problem of street children that happen in Semarang City. This study is using qualitative descriptive through interviews, literature, and document, and also SWOT analysis (Strength, Weakness, Opportunities, Threats) that used for analyze.The results obtained that handling problem of street Children by the Social Department of Youth and Sports in Semarang city is not maximized. Where there still an obstacles such as deficieny of human resources,minimum budget, insufficient infrastructure, the habit of society that hard to be change and the absence of regulation of mayor. By analyzing the internal environment and the external environment we can got the strategies that will test by litmus test to determine the level of strategical from these issues. Based on these results, It is reccomended for the strategic issues that has formulated can help Social Service of Youth and Sports of Semarang city for handling the problem of street children. This is done to improve the handling of children street problem in Semarang City.